Aktualne normy okulistyczne dla kierowców – jak Polska wypada na tle innych państw? - Stopyra, Wiktor (Klinika Oczna / Acta Ophthalmologica Polonica, 2020)
To drive a car it is necessary to demonstrate both relevant technical skills and knowledge as well as adequate health, especially of the eyes. The correct criteria of visual parameters for drivers are approved by the Minister of Health in Poland. In the past five years, medical guidelines for applicants and drivers have changed three times. First of all, attempts were made to adapt national regulations to the recommendations of the European Union. This paper is an attempt to answer to what extent this plan has been implemented. The article presents the minimum ophthalmological criteria currently applicable in Poland to drivers and candidates for drivers. It was based on the guidelines contained in the current Ordinance of the Minister of Health dated August 30th, 2019 on medical examinations of applicants for a driving licence and drivers. The results were compared with the latest recommendations of the European Union updated on July 22nd 2018. Standards in several major European countries (Germany, France, the UK, Italy, Spain, Switzerland) as well as examples of US states (California, New York, Florida, Texas, Illinois, DC) and other global powers were also analysed (Japan, Canada, Australia, Israel, India, Mexico). The most important functions of the eye were examined, including visual acuity, visual field, color vision, binocular vision, glare sensitivity, mesopic vision and contrast sensitivity. The results are collected in the appropriate tables.